Insights into the Acid-Induced Gelation of Original Pectin from Potato Cell Walls by Gluconic Acid-δ-Lactone - Dandan Lei; Likang Qin; Mei Wang; Haoxin Li; Zunguo Lei; Nan Dong; Jia Liu (Foods, 2023)
The acid-induced gelation of pectin in potato cell walls has been gradually recognized to be related to the improvement in the cell wall integrity after heat processing. The aim of this study was to characterize the acid-induced gelation of original pectin from a potato cell wall (OPP). Rheological analyses showed a typical solution–sol–gel transition process of OPP with different additions of gluconic acid-δ-lactone (GDL). The gelation time (Gt) of OPP was significantly shortened from 7424 s to 2286 s. The complex viscosity (η*) of OPP gradually increased after 4000 s when the pH was lower than 3.13 and increased from 0.15 to a range of 0.20~6.3 Pa·s at 9000 s. The increase in shear rate caused a decrease in η, indicating that OPP belongs to a typical non-Newtonian fluid. Furthermore, a decrease in ζ-potential (from −21.5 mV to −11.3 mV) and an increase in particle size distribution (from a nano to micro scale) was observed in OPP after gelation, as well as a more complex (fractal dimension increased from 1.78 to 1.86) and compact (cores observed by cryo-SEM became smaller and denser) structure. The crystallinity of OPP also increased from 8.61% to 26.44%~38.11% with the addition of GDL. The above results call for an investigation of the role of acid-induced OPP gelation on potato cell walls after heat processing.